Selection of latrine sites by Himalayan musk deer (Moschus leucogaster) in Neshyang Valley, Annapurna Conservation Area, Nepal - Paras Bikram Singh; Bhakta Bahadur Shrestha; Arjun Thapa; Pradip Saud; Zhigang Jiang (Journal of Applied Animal Research, 2018)
Musk deer is threatened by poaching for musk pod and habitat fragmentation. The species is endangered within its distribution range including Nepal, Bhutan, India, Pakistan, Mongolia, China, Korea and Russia. In Nepal, the deer is confined to protected areas throughout the Himalaya. It is a solitary and shy forest dweller with a crepuscular activity pattern. It prefers and repeatedly uses one or more specific defecation sites. Such behaviour is believed to function in chemical communication among individuals. This study was conducted in Neshyang valley in the Annapurna Conservation Area, and aims to evaluate how musk deer selects the latrine site in its habitat taking into account both biotic and abiotic factors. In order to achieve this aim, we laid out a total of 23 transects of 500 m length throughout the study area. Within each transect, 20 m × 20 m nested structured quadrats were located at an interval of 100 m. We found that musk deer preferred to use latrine sites in fir forest while they avoid both blue pine forest and open areas. Furthermore, distance from water sources and mixed forests have a crucial role in selecting latrine sites by musk deer.